Exquisite wonder: Colour film, realism and the Yankee voyage, 1936‐38. Issue 1 (1st May 2020) - Geiger, Jeffrey
This article looks at rare Kodachrome film taken across Oceania, mostly shot by a skilled amateur filmmaker, Edmund Zacher, to document the circumnavigation of the famous clipper Yankee. There are three intertwined lines of inquiry traced here. The first explores relations between US imperialism, moving image media and a popular imaginary, considering how experiences of virtual travel engage with cultural ideology. The second examines how this footage may be interpreted: how might critical frameworks brought to bear on amateur non-fiction differ from those commonly applied to professional and narrative fiction film? A key reference point is the theory of cinematic gesture developed by Giorgio Agamben, who expands on the work of Gilles Deleuze and his notion of the movement image. This stress on gesture and on the mediality of moving images leads towards a third key area under consideration: colour and the (then) new medium of Kodachrome. Homing in on relations between colour stock and motion picture realism, this study explores the ways that Kodachrome colour might have affected broader perceptions of the world itself.